On the Complexity of Scheduling MIMD Operations for SIMD Interpretation - Fan, X.Z.; Abughazaleh, N.B.; Wilsey, P.A. (Journal of parallel and distributed computing, 1995)
Programming SIMD hardware to interpret (in parallel) programs and data resident in each PE is a technique for obtaining a cost-effective massively parallel MIMD processing environment. The performance of the synthesized MIMD environment can be greatly improved by with a variable instruction interpreter that delays the interpretation of infrequent operations. In this paper, the process of building a variable instruction interpreter that optimizes an objective function is examined. Two different objective functions are considered, namely, maximizing the total instruction throughput (called Maximal MIMD Instruction Throughput, MMIT) and maximizing overall PE utilization (called Maximal MIMD PE Utilization, MMPU). We show that the decision version of both the MMIT and MMPU problems is NP-complete.